2008
DOI: 10.1016/j.taap.2008.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA damage and its repair in rat spleen following subchronic exposure to aniline

Abstract: The mechanisms by which aniline exposure elicits splenotoxic response, especially the tumorigenic response, are not well-understood. Splenotoxicity of aniline is associated with iron overload and generation of reactive oxygen species (ROS) which can cause oxidative damage to DNA, proteins and lipids (oxidative stress). 8-Hydroxy-2'-deoxyguanosine (8-OHdG) is one of the most abundant oxidative DNA lesions resulting from ROS, and 8-oxoguanine glycosylase 1 (OGG1), a specific DNA glycosylase/lyase enzyme, plays a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
1
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(104 citation statements)
references
References 47 publications
7
87
1
7
Order By: Relevance
“…9,10,21,25,[29][30][31][32][33] One of the important and sensitive indicators of DNA damage and a well-validated biomarker, resulting from oxidative stress, is the DNA guanine base oxidation product 8-OHdG, which was also studied in other publications. 9,19,21,34 The findings of our study are in concordance with Matsuzaki et al and Yamaguchi et al, who stated that patients with endometriosis have higher amounts of 8-OHdG-DNA damage compared to controls. Using high performance liquid chromatography electrochemical technique, Kao et al also showed higher levels of 8-OHdG in patients with endometriosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…9,10,21,25,[29][30][31][32][33] One of the important and sensitive indicators of DNA damage and a well-validated biomarker, resulting from oxidative stress, is the DNA guanine base oxidation product 8-OHdG, which was also studied in other publications. 9,19,21,34 The findings of our study are in concordance with Matsuzaki et al and Yamaguchi et al, who stated that patients with endometriosis have higher amounts of 8-OHdG-DNA damage compared to controls. Using high performance liquid chromatography electrochemical technique, Kao et al also showed higher levels of 8-OHdG in patients with endometriosis.…”
Section: Discussionsupporting
confidence: 93%
“…When the hydroxyl radicals reach the DNA they cause a base oxidation product 8-hydroxy-2-deoxyguanosine (8-OHdG) modifying the structural properties of DNA bases and thus damaging the DNA. [19][20][21] This marker has been used to estimate the progression of many diseases and in the promotion of carcinogens. 22,23 There are 3 types of defense against formation of ROS: (1) enzymatic inactivation: in order to access the first line of oxidative stress defense we evaluated the concentration of total antioxidant capacity (TAC).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that the involvement of oxidative stress in AA-induced toxicity. 8-OHdG, one of the major abundant oxidative DNA damage markers which can efficiently repair by a glycosylase, OGG1 (62)(63)(64)(65). In this study, gene expression of OGG1 was decreased in cells exposed to AA.…”
Section: ------------------------------------------------------------mentioning
confidence: 48%
“…Uszkodzone erytrocyty są wychwytywane głównie przez śledzionę, co może prowadzić nie tylko do uwolnienia aniliny i/lub jej metabolitów w tym narządzie, lecz także do nagromadzenia żelaza w wątrobie (hemosyderoza), co z kolei może powodować: peroksydację lipidów, utlenianie białek (Khan i in. 1997;1997a;1999;2003a;2003b;2003c) i DNA (Ma i in. 2008).…”
Section: Mechanizm Działania Toksycznegounclassified